HUBUNGAN SANITASI LINGKUNGAN DAN HIGIENE PERORANGAN DENGAN KELUHAN PENYAKIT SKABIES PADA ANAK-ANAK DI PANTI ASUHAN AMALIYAH KOTA KENDARI TAHUN 2019 - Nur Nazila Fitria Fitri; Ramadhan Tosepu; Nurmala Dewi (Jurnal Kesehatan Masyarakat Celebes, 2020)
Disease scabies is a skin disease caused by a parasitic mite Sarcoptes scabiei that seeks to establish a tunnel under the skin and is transmitted through direct human contact. Kendari City Health Department data showed an infection of skin disease is always in the top 20 diseases. Data in 2016 that infectious skin disease was ranked 13th with a prevalence of 2.82%, in 2017 infectious skin disease was ranked 14th with a prevalence of 1.93% and in 2018 the infectious skin disease was ranked 11th with a prevalence of 3.20%.research aimsto determine the relationship between environmental sanitation and personal hygiene complaints scabies disease in children in the orphanage Amaliyah Kendari City in 2019, This type of research isanalyticwith cross sectional approach with total population of 200 children, sampling techniquepurposive sebanya sampling 134 children. Analysis of the data used is the chi-square analysis. The results showed no relationship between the provision of clean waterwith symptoms of scabies disease(p-value= 0.725)There was no correlation between the use of latrines Scabies is a disease with symptoms(p-value= 0.725), there was no relationship between sewerage (SPAL) with symptoms of scabies disease(p-value = 0.725), there was no relationship between landfills with complaints Scabies disease (p-value= 0.481) and there was a relationship between personal hygiene illness complaints Scabies(p-value= 0.000). Keywords : Environmental Sanitation, Personal Hygiene and Scabies.